(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Background: Sepsis has a high mortality rate and an effective and inexpensive clinical indicator is important to determine prognosis in these patients. The objective of the study was to study serum blood urea nitrogen to albumin ratio as a prognostic factor for in-hospital mortality in patients admitted with sepsis. Subjects and methods: A retrospective cohort study was conducted at Mayo Hospital Lahore. One-hundred and sixty-eight adult patients admitted between March 2022 to March 2023 were included. Data was obtained from medical records. Blood urea nitrogen to albumin ratio was noted along with other co-morbidities and probable infection source. Outcome was noted in the form of discharge or expiry. Univariable and receiver operating characteristics curve analysis was carried out. The results were further verified by multivariate logistic regression analysis to evaluate the independent predictive value of the ratio. Results: Among 168 participants, majority were males with a mean age of 55 years. One-hundred and seven patients were discharged and 61 expired. All-cause mortality was seen higher in patients with higher blood urea nitrogen to albumin ratio (p-value<0.028). The area under the receiver operative (ROC) curve (AUC) was 0.682 [95% CI=0.600-0.765]. A cut-off value of the BUN to albumin ratio was >9.524 calculated from the ROC curve was found to have a sensitivity of 77.0% and specificity of 44.1%. This AUC for BUN-to-albumin ration was more than BUN or albumin alone. Conclusion: Blood urea nitrogen to albumin ratio at admission is significantly associated with in-hospital mortality in patients with sepsis.